Prepatellar Bursal Infection Caused by Mycobacterium tuberculosis with an In Situ Total Knee Arthroplasty: A Case Report and Comprehensive Literature Review - Abdulrahman D. Algarni (Case Reports in Infectious Diseases)
Prepatellar bursal infection is a rare occurrence. The incidence of tuberculosis, including musculoskeletal type, is increasing. We present a case of isolated prepatellar bursal swelling associated with a discharging sinus; the condition developed in an elderly patient 4 years after total knee arthroplasty. Aspiration of the bursa revealed acid-fast bacilli on Ziehl–Neelsen staining, typical of Mycobacterium tuberculosis; this was confirmed later on culture. The patient was successfully treated with a 6-month course of antituberculous chemotherapy. To the best of our knowledge, only two previous cases of tuberculous prepatellar bursal infection have been reported in English literature. Our case illustrates the importance of considering tuberculous prepatellar bursal infection in the differential diagnosis of anterior knee swelling. All physicians treating patients with musculoskeletal disease should be aware of the possibility of this diagnosis and maintain a high index of suspicion; this is especially true in areas where tuberculosis is still endemic and in high-risk patients, such as the elderly.